MOBILE MEDIA LITERATURE APPLICATION FOR IDENTIFICATION OF STUDENT'S READING INTEREST - Usman Nurhasan; Erninda Ristiani; Samsul Islam Baddrisshofa (Kresnamedia Publisher, 2021)
The School Literacy Movement (GLS) aims to foster youth character through a culture of literacy (reading and writing). However, in the presence of the Covid-19 outbreak, Indonesian education needs to use online media to keep learning going. Many types of platforms are used for online learning media, but all of these media do not support school literacy activities, so school literacy activities do not run as usual. Based on these problems, a solution was created, namely an application that makes it easy for literacy activities to take place online. Students can access this application to do online literacy via a laptop or smartphone. This application makes it easier for teachers to monitor the course of online literacy programs. The results of this study are indicated by functional testing on all features obtaining a 100% valid percentage. Tests on users get an average percentage of more than 80%. The test results prove that this application can be accepted by students, teachers and admins at State High School 1 Geger Madiun to make literacy activities more effective and efficient.